2018
DOI: 10.1016/j.jmoldx.2017.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Diagnostic Utility of a High-Risk Human Papillomavirus PCR Test on Formalin-Fixed, Paraffin-Embedded Head and Neck Tumor Tissues

Abstract: The increasing prevalence of high-risk human papillomavirus (HR-HPV)-associated head and neck squamous cell carcinoma (HNSCC) has prompted strong clinical demands for detecting HR-HPV directly in the tumor. Although p16 immunohistochemistry (IHC) has been the standard testing method, it has limitations including false positivity, lack of sensitivity in low tumor cell samples such as fine-needle aspirate (FNA), and its subjectivity. We developed a modified method based on a commercial automated HR-HPV PCR assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…2 Recently, several studies have suggested that the Roche cobas 4800 (Roche Diagnostics USA, Indianapolis, Indiana) platform be used to determine HPV-positivity in formalin-fixed, paraffin-embedded tissue, although that would require further validation. [16][17][18] PREVALENCE AND TYPES OF HPV IN OROPHARYNGEAL CARCINOMAS The authors of a large international study stringently defined the criteria for HPV-positivity in head and neck cancer as a combination of positivity for HPV-DNA and either HPV E6 mRNA or p16 as biomarkers. 12 Using those criteria, they found that 22% of oropharyngeal carcinomas (anatomic site not further defined) were HPV þ .…”
Section: Methods For Determining Hpv-positivitymentioning
confidence: 99%
“…2 Recently, several studies have suggested that the Roche cobas 4800 (Roche Diagnostics USA, Indianapolis, Indiana) platform be used to determine HPV-positivity in formalin-fixed, paraffin-embedded tissue, although that would require further validation. [16][17][18] PREVALENCE AND TYPES OF HPV IN OROPHARYNGEAL CARCINOMAS The authors of a large international study stringently defined the criteria for HPV-positivity in head and neck cancer as a combination of positivity for HPV-DNA and either HPV E6 mRNA or p16 as biomarkers. 12 Using those criteria, they found that 22% of oropharyngeal carcinomas (anatomic site not further defined) were HPV þ .…”
Section: Methods For Determining Hpv-positivitymentioning
confidence: 99%
“…Thus, establishing an accurate and reliable method of HPV detection in cytologic samples is critical [31]. Table 2 summarizes the many of the studies conducted in recent years comparing commercially available tests for their performance in HNSCC specimens [28,[32][33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Hpv Detection Technologiesmentioning
confidence: 99%
“…These techniques are known to be stable and reproducible, and a recent meta-analysis found the pooled sensitivity and specificity of HPV DNA PCR to be respectively 98 and 84% for HPV detection in OPSCCs ( 49 ). However, FFPE samples are often the only material available for molecular testing after pathological examination in the OPSCC context and only few studies have evaluated different commercial molecular assays on head and neck FFPE biopsies ( 50 55 ). Regarding the frequent proportion of degraded DNA in FFPE samples, some authors such as Steinau et al suggest to pretreat FFPE tissues using specific protocols to enhance DNA extraction yields before PCR assay ( 56 ).…”
Section: Main Techniques Used To Detect Hpv In Opsccmentioning
confidence: 99%